Distribution Analysis and Distribution of 3 Kg LPG Gas Sales Allocations (Case Study Of PT. Sintora Putra Gasindo) - Indah Aryani; Wahyu Syarvina (Penerbit Jurnal Indonesia, 2022)
LPG (liquefied petroleum gas) is one of the petroleum products produced by PT Pertamina (Persero). The government has implemented a national energy policy by converting kerosene to LPG. In 2007, the government started converting kerosene into 3 kg LPG. In order to overcome the scarcity of 3 kg LPG, Pertamina and the government have begun to improve, one of which is by changing the 3 kg LPG distribution system from an open distribution system to a closed distribution system. This is to reduce oil subsidies, the largest portion of which is 50% of the government's energy subsidies, and each year the subsidies continue to increase. PT Pertamina (Persero) launched its product with a new variant of 3 kg LPG packaging which is fully subsidized by the government so that kerosene consumers can switch to LPG. With the issuance of the conversion policy, all kerosene trading agents became agents of 3 kg LPG. PT. Sintora Putra GasIndo is a company engaged in gas distribution for 3 kg of gas. PT. Sintora Putra GasIndo distributes its products in several areas of Deli Serdang. To market their products, companies need a marketing system, namely distribution channels that must be studied, so that companies can earn big profits in certain areas in the Deli Serdang area. Regarding the objectives to be achieved, namely the efficiency and effectiveness of the company and the use of available resources. Competition in the market is getting tougher and products can be widely available in several areas of Deli Serdang. Regarding the objectives to be achieved, namely the efficiency and effectiveness of the company and the use of available resources. Competition in the market is getting tougher and products can be widely available in several areas in the Deli Serdang area.